Increasing the competitiveness of herbal beverage products garuda women farmer group, Cipayung Village, South Tangerang City through understanding of accounting and taxation digital based - Devid Putra Arda; Aep Saefullah; Ahmad Fadli; Fisy Amalia (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
This Community Service activity captures the increase in the competitiveness of home industry herbal drink products. This activity is motivated by a strong desire to encourage women farmers who join the Garuda Women Farmers Group (KWT) in Cipayung Village, South Tangerang City to increase awareness and understanding of the importance of knowledge of accounting and taxation. as a pillar of business success . In the end , KWT is also one of the manufacturers of herbal drinks for health and fitness with a brand "samilakor" is able to understand and compile simple financial reports, as well as understand the intricacies of taxation for MSME actors . Including understanding tax calculations as a basis for determining the amount of tax payable. Understanding of accounting and taxation is expected to be mastered after participating in this activity. The facts show that MSME business actors in the City of South Tangerang encounter many obstacles in applying standard accounting practices, as a basis for presenting fair financial reports. Another problem, MSME players experience problems understanding and complying with tax obligations. The main causes of the inability to understand and comply with accounting principles and tax regulations are due to the low level of education of MSME actors, and disciplinary backgrounds that are irrelevant to the preparation of financial and tax reports. This condition is exacerbated by the lack of training for MSME actors regarding the business development they run and the skills to record business transactions. The training method applied is face-to-face, including lectures, discussions, case studies, and questions and answers. The training materials are in the form of modules containing accounting and tax materials for MSMEs. The accounting report material contains an understanding of the accounting cycle, which is ultimately able to compile financial reports. Furthermore, material for the preparation of practical financial reports based on the Excel application is given. After the participants understand preparing standard financial reports, they are then introduced to the Standards for Financial Accounting for Micro, Small and Medium Entities ( SAK EMKM ). This accounting standard was introduced to participants, intended to provide an understanding that in preparing financial reports it must be guided by financial accounting standards determined by professional organizations, in this case the Indonesian Institute of Accountants (IAI). For taxation material , Law Number 7 of 2021 concerning Harmonization of Tax Regulations (UU HPP) which regulates the latest MSME tax regulations is explained. The training in the PkM activity was attended by participants from MSME actors in the South Tangerang City area and its surroundings, with the number of participants total 40 people. In order to assess the success of the training, participants were asked to give a score by completing the pre-test and post-test . Then the score is analyzed to determine the effectiveness of the activity. The results of the activity show that this training has been running quite effectively. Participants can understand the preparation of cash flows and understand the accounting and taxation of MSMEs and their calculations quite adequately